2013
DOI: 10.1002/2012ja018468
|View full text |Cite
|
Sign up to set email alerts
|

Global view of inner magnetosphere composition during storm time

Abstract: [1] Plasma dynamics in the inner magnetosphere are greatly affected by variations in the ion composition. The ratio of hydrogen to oxygen has been shown to be highly dependent on geomagnetic activity. To investigate this dependence, we examine the timing of the injection and subsequent evolution of O + in the ring current during the storm of 6 August 2011 as observed by Two Wide-angle Imaging Neutral-atom Spectrometers (TWINS) instruments. To help interpret magnetospheric evolution using the global O Energetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…Since first suggested by Shelley et al [], the dynamics leading to the ionospheric outflow of O + ions and the impact on the evolution of the magnetosphere‐ionosphere system have been the subject of numerous studies [e.g., Schunk and Raitt , ; Mukai et al , ; Schunk and Sojka , ; Seki et al , ; Daglis et al , ; Winglee et al , ; Nosé et al , ; Barakat and Schunk , ; Glocer et al , ; Garcia et al , ; Glocer et al , ; Ilie et al , , ]. For instance, several studies [e.g., Young et al , ; Hamilton et al , ; Daglis et al , ; Fu et al , , ; Winglee et al , ; Kozyra et al , ; Nosé et al , ] find that O + can dominate not only the mass density but even the number density in the magnetosphere, therefore controlling the large‐scale processes of mass and energy flow through geospace.…”
Section: The Neglected Component Of Ionospheric Outflow: Nitrogen Ionsmentioning
confidence: 99%
“…Since first suggested by Shelley et al [], the dynamics leading to the ionospheric outflow of O + ions and the impact on the evolution of the magnetosphere‐ionosphere system have been the subject of numerous studies [e.g., Schunk and Raitt , ; Mukai et al , ; Schunk and Sojka , ; Seki et al , ; Daglis et al , ; Winglee et al , ; Nosé et al , ; Barakat and Schunk , ; Glocer et al , ; Garcia et al , ; Glocer et al , ; Ilie et al , , ]. For instance, several studies [e.g., Young et al , ; Hamilton et al , ; Daglis et al , ; Fu et al , , ; Winglee et al , ; Kozyra et al , ; Nosé et al , ] find that O + can dominate not only the mass density but even the number density in the magnetosphere, therefore controlling the large‐scale processes of mass and energy flow through geospace.…”
Section: The Neglected Component Of Ionospheric Outflow: Nitrogen Ionsmentioning
confidence: 99%
“…Global regions of O + were found to comprise islands of smaller structure. Ilie, Skoug, Valek, et al () compared TWINS oxygen images with a global model and found that plasmoids may be a major mechanism for O + transport and loss.…”
Section: Scientific Results From 2013 To 2017mentioning
confidence: 99%
“…Physics‐based models offer a means of interpreting the images to discover which mechanisms are controlling the dynamics. Numerous TWINS‐based studies have included global models in this way (Buzulukova et al, ; Fok et al, ; Glocer et al, ; Ilie, Skoug, Valek, et al, ; McComas et al, ).…”
Section: Scientific Results From 2013 To 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…During periods of strong solar driving, O + of ionospheric origin drastically increases in the plasma sheet and geosynchronous locations [e.g., Young et al , ; Lennartsson and Shelley , ; Nosé et al , ; Nosé , ; Denton et al , ] and the inner magnetosphere [ Sharp et al , ; Hamilton et al , ; Daglis et al , ; Kozyra , ; Kronberg et al , ]. Ring current modelers have switched from using basic empirical models of plasma sheet composition [e.g., Fok et al , ; Jordanova et al , ; Kozyra et al , ; Liemohn et al , ; Ebihara and Ejiri , ; Jordanova et al , ] to dynamic, physics‐based models that capture the evolution from outflow to plasma sheet [ Moore , ; Moore et al , ; Fok et al , ; Welling et al , ; Ilie et al , ]. It has been found that spatial and temporal dynamics of the ionospheric source are important in controlling ring current development and are distinct from the solar source.…”
Section: Introductionmentioning
confidence: 99%